Nurses' experiences of the effects of mindfulness training: A narrative review and qualitative meta-synthesis. (May 2021) - Wu, Xiaxin; Hayter, Mark; Lee, Amanda J.; Zhang, Yu
Abstract: Objective: To explore nurses' experiences of the effects of undertaking mindfulness training. Design: Qualitative meta-synthesis. Data sources: Qualitative literature from seven scientific databases: Pubmed, Cochran Library, Science Direct, EBSCO, Web of Science, Scopus and PsycINFO were searched. Review methods: The PRISMA flow diagram was used to report the phases of the literature search. The Critical Appraisal Skills Program (CASP) qualitative research checklist, and the Mixed-Methods Appraisal Tool (MMAT) for mixed method studies were used as appraisal framework. Data synthesis was conducted using Thematic synthesis. The review steps were guided by Adams, Chamberlain, & Giles, 2019 and Whittemore & Knafl, 2005. Results: 4 qualitative studies and 3 mixed-methods studies were included in the review. Four interpretive themes were generated to show how nurses experience of the effects of mindfulness training: 1. Stress conceptualisation and management; 2. Nurses' valued aspects of mindfulness training strategies; 3. Self-care awareness and strategies; 4. Challenges of mindfulness training. Conclusion: Conducting mindfulness-based interventions among nursing professionals helps to reduce work-related stress and has positive effects on work and life.